Modo de viver dos/as moradores/as da ecovila Tibá de São Carlos: processos educativos emergentes - Melges, Alice Maria Calado (Universidade Federal de São Carlos, 2022)
Ecovillages represent a resistance movement to the dominant system that questions the values of modern society by leading ways of life and coexisting that are guided by community and ecological principles. The Tibá ecovillage, located in São Carlos/SP, seeks to implement more harmonious human/nature relationships based on the ethical and political principles of Permaculture. This research, based on references that discuss utopia, praxis, dialogicity, the Epistemologies of the South, the ecology of knowledge, the sociology of absences and emergencies and the Pedagogy of care, assumes as its central objective to identify and understand the educational processes emerging from the way of life of the residents of this ecovillage. This investigation consists of qualitative research which, inspired by Phenomenology, sought to understand the phenomenon studied through the perspective and experience lived by residents of the Tibá ecovillage. It was based on conducting semi-structured interviews, using a script with five open questions. Seven socio-residents of the community were interviewed. Data were analyzed following the procedures of Phenomenology, situated phenomenon modality, according to Martins and Bicudo (2005) and Gonçalves Junior et al. (2021). Data analysis revealed that the way of life of residents in the ecovillage is organized around three axes that make up three categories of analysis: “We had a desire and that became a proposal”, “Trying to understand the other for this coexistence to work” and “A peaceful place to live, closer to nature”. These categories respectively denote the values and utopia that guide the praxis of the interviewed group and the lived experiences related to community life and life in the countryside. The educational processes identified by the research are triggered by these two contexts of experience and the way they are articulated to principles, ethics and values arising from Permaculture. Cooperation, diversity, otherness and care are key components of the educational processes that emerge from this way of living, considering human relationships and relationships with nature. We believe that they can contribute and inspire the construction of an alternative education and society project based on the idea of cooperation and care.
Way of living of Tibá ecovillage residents: emerging educational processes
Keywords: Processos educativos; Modo de viver; Ecovila; Práxis comunitária; Permacultura; Educative processes; Way of life; Ecovillage; Community praxis; Permaculture; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO